Describing The Relationship Between Text Habits And Spelling Competency Among Bsed English Students - Yangyang, Stephanie Rosales; Pesalbon, Marian Duca; Suarez, Aris Pet Angeli; Naparan, Genesis (Beyond Words, 2024)
This research determined the relationship between texting habits and spelling competency among second-year BSEd English major students. The study employed a quantitative research design to gather data. The researchers created a questionnaire specifically related to texting habits and an adapted Civil Service questionnaire to measure spelling competency. Results showed that students exhibited a high frequency of texting, but displayed below-average spelling competencies. For future research, it is recommended to use a combined quantitative and qualitative design to gain deeper insights into students' opinions, attitudes, and practices regarding texting and spelling. Additionally, future studies should consider including participants from various other courses, not just English majors, to broaden the scope of the research.